2013
DOI: 10.1186/1471-2164-14-390
|View full text |Cite
|
Sign up to set email alerts
|

Pyrosequencing analysis of the human microbiota of healthy Chinese undergraduates

Abstract: BackgroundElucidating the biogeography of bacterial communities on the human body is critical for establishing healthy baselines from which to detect differences associated with disease; however, little is known about the baseline bacterial profiles from various human habitats of healthy Chinese undergraduates.ResultsUsing parallel barcoded 454 pyrosequencing targeting on the 16S rRNA gene V3 region, the bacterial diversity of the nasopharynx, saliva, dominant hands, and feces were investigated from 10 healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
88
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(103 citation statements)
references
References 70 publications
13
88
0
2
Order By: Relevance
“…Also, because occupants have a great impact on the indoor air microbiomes, variations in microbiomes of different population groups may influence air microbial assemblages (24), a phenomenon that has been reported in studies investigating indoor surfaces (22,53). One of the common genera detected in this study, Enhydrobacter, is a documented resident on the human skin but may be present in higher proportions in Chinese individuals (44). Such observations underscore the need to take the occupants' microbiomes into account when examining indoor microbial assemblages.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Also, because occupants have a great impact on the indoor air microbiomes, variations in microbiomes of different population groups may influence air microbial assemblages (24), a phenomenon that has been reported in studies investigating indoor surfaces (22,53). One of the common genera detected in this study, Enhydrobacter, is a documented resident on the human skin but may be present in higher proportions in Chinese individuals (44). Such observations underscore the need to take the occupants' microbiomes into account when examining indoor microbial assemblages.…”
Section: Discussionmentioning
confidence: 75%
“…For example, soil-dwelling genera, such as Arthrobacter and Psychrobacter, which were among the common genera documented in NYC, all were detected at Ͻ0.5% across the Hong Kong data set. Conversely, Enhydrobacter, a genus previously detected in high proportions in Chinese young adults (44), were among the top skin-associated genera on the MTR but not considered to be a common genus in the NYC subway. Such differences call for the additional metagenomic analysis of subway systems around the world to determine whether additional geographical and/or cultural/ethnic factors play roles in driving differences in aerosol microbiomes.…”
Section: ϫ10mentioning
confidence: 99%
“…Eleven phyla and two candidate divisions (TM7 and OD1) were found. Three phyla (Firmicutes, Bacteroidetes, and Proteobacteria) were the most predominant in infancy fecal samples and comprised Ͼ97% of all sequences, which showed a higher proportion of Proteobacteria in infants than in adults (26). In total, sequences from fecal microbiota could be classified as 270 genera, with 237 genera in healthy infants and 183 genera in infants with FA.…”
Section: Resultsmentioning
confidence: 94%
“…Species belonging to the genus Rothia have been repeatedly described as being members of oral communities associated with periodontal health (26)(27)(28)(29)(30)(31) or at least as being more predominant in health (28). In the same way, Corynebacterium appeared to be more associated with healthy subgingival biofilm (32,33). Moreover, Rothia and Corynebacterium were among the bacteria that showed the greatest increases after periodontal treatment (34), while a study suggested that Corynebacterium might be considered a putative periodontal protector (35).…”
Section: Discussionmentioning
confidence: 94%